"Flash" Annealing in a Cold‐Rolled Low Carbon Steel Alloyed with Cr, Mn, Mo, and Nb: Part II—Anisothermal Recrystallization and Transformation Textures. Issue 1 (8th October 2018) - Castro Cerda, Felipe Manuel; Kestens, Leo A. I.; Petrov, Roumen H.
Abstract : The aim of the present investigation is to study the microstructure and texture evolution in a cold‐rolled low carbon steel subjected to continuous heating and subsequent quenching. Peak‐annealing and quenching experiments are carried out at different temperatures at three heating rates (10, 400, and 1000 °C s −1 ). The texture evolution in ferrite and martensite is analyzed separately via Electron Backscattered Diffraction (EBSD) measurements. It is observed that the recrystallization is virtually completed at 771 °C in samples heated at 10 °C s −1 . Conversely, the recrystallization is suppressed in samples heated at rates ≥400 °C s −1 . In samples heated at 10 °C s −1, the ferrite texture evolves according to the well‐known recrystallization behavior, showing a maximum in 113<110> components, whereas in samples heated at rates ≥400 °C s −1, the texture is similar to the one of the cold‐rolled material. It is concluded that the texture evolution in martensite is strongly dependent on the evolution of recrystallization textures in ferrite. A particular grain substructure product of the interaction between the recrystallization of ferrite and massive austenite formation is observed after heating at rates ≥400 °C s −1 . However, this substructure seems to have effect neither on the textures of ferrite nor on the work hardening behavior. Abstract : The heating rate impacts considerably the recrystallization behavior and texture evolution in ferrite and martensite. At relatively slow heating rates (10 °C s–1), the recrystallization of ferrite is almost complete before the onset of austenite formation. At elevated heating rates (>400 °C s–1), the austenite nucleation is likely to occur in non‐recrystallized ferrite, thereby influencing the texture of martensite.